Penerimaan Diri Orang Tua dengan Anak Down Syndrome : Literature Review - Kadek Merly Reza Tresnaugi; Luh Kadek Pande Ary Susilawati (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Parents always want ideal, healthy, and normal children, but there is a possibility that a child will be born with special needs, one of which is Down syndrome. Children who are different from their parents usually have an impact on their self-acceptance. This study aims to determine how parents accept children with Down syndrome. A literature review based on sources, namely journal articles published from 2015 to 2023, was used in this study. Using the Google Scholar database, you can search for journal articles using keywords such as Self-Acceptance, Parents, Children with Special Needs, and Down Syndrome. The results of the study show that the researchers selected 70 articles according to the criteria and obtained 10 journal articles. According to the ten journals, parents must go through four stages in accepting their child's condition of having Down syndrome, namely the stage of denial, the stage of conflict, the stage of adjustment, and the stage of acceptance. On the other hand, one journal states that self-acceptance consists of three stages, namely the stage of denial, the stage of adjustment, and the stage of acceptance. According to this study, self-acceptance is very important for parents with children with Down syndrome because it allows them to accept and embrace their child's condition as a whole. Accepting oneself is a difficult process and takes a long time.